1976
DOI: 10.1111/j.1365-2265.1976.tb03836.x
|View full text |Cite
|
Sign up to set email alerts
|

INHIBITORY ACTIVITY OF ANALOGUES OF LUTEINIZING HORMONE‐RELEASING HORMONE (LH‐RH) IN VITRO AND IN VIVO

Abstract: Improved inhibitors of LH-RH are those which, beside removal of the histidine residue at position 2 of LH-RH, include replacement of glycine at position 6 by a D-amino acid. A still better modification is replacement of the histidine residue at position 2 by D-phenylalanine. As examples, when tested in pituitary cells in culture, [Des-His2]LH-RH, [Des-His2, D-Leu6]LH-RH, [Des-His2, D-Phe6]-LH-RH, [D-Phe2]LH-RH, [D-Phe2, D-Leu6]LH-RH and [D-Phe2, D-Phe6]LH-RH inhibit 50% of LH release induced by LH-RH at molar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

1977
1977
1982
1982

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…Measurement of Biological Activity and Calculations. The agonistic and antagonistic activities of the LH-RH analogs were measured as the potency of the peptides to stimulate and inhibit, respectively, the LH-RH-induced LH release in rat anterior pituitary cells in primary culture (23)(24)(25). Kd values for LHreleasing activity were determined as the peptide ED5o for LH release.…”
mentioning
confidence: 99%
“…Measurement of Biological Activity and Calculations. The agonistic and antagonistic activities of the LH-RH analogs were measured as the potency of the peptides to stimulate and inhibit, respectively, the LH-RH-induced LH release in rat anterior pituitary cells in primary culture (23)(24)(25). Kd values for LHreleasing activity were determined as the peptide ED5o for LH release.…”
mentioning
confidence: 99%
“…It is well known from previous investigations on the pharmacology of narcotics that narcotic drugs affect the secretion of several pituitary hormones, including prolactin, growth hormone, vasopressin, and adrenocorticotropic hormone (ACTH). Morphine is a potent releaser of prolactin, growth hormone, and vasopressin (1)(2)(3)(4). Recently, it has been shown that enkephalin analogs can also increase blood prolactin levels (5).…”
mentioning
confidence: 99%
“…These agonist properties were only weakly present; the potency of the compound was estimated to be less than 1% of that of native bPTH-(1-84) on a molar basis [3]. Similar difficulties have been encountered in other hormone systems when antagonists that were potent in vitro were brought to evaluation in vivo [24][25][26][27][28]. The reasons for the discrepancy between agonist and antagonist responses in vitro and in vivo remain to be elucidated.…”
Section: Discussionmentioning
confidence: 83%